Multi-channel security protocols in personal networks - Huang, X (2014)
Personal computing devices are becoming more and more popular. These devices are able to collaborate with each other using wireless communication technologies, and then support many applications. Some interesting examples of these are healthcare, context-aware computing, and sports training. In any such applications, security is of vital importance. Firstly, sensitive personal data is always collected in these applications, thus confidentiality is usually required. Secondly, authenticity and integrity of data or instructions are always critical; incorrect data or instructions are not only useless, but also harmful in some cases. This thesis analyses the security requirements of personal networks, and develops a number of multi-channel security protocols. With the help of out-of-band channels, especially no-spoofing and no-blocking out-of-band channels, these protocols can bootstrap security in personal networks. In particular, three kinds of security protocols have been studied: protocols that use human-controlled channels, protocols that use visible light communications, and protocols that use intra-body communications. Interesting trade-offs have been discovered among communication, computation and security, resulting from different channel implementations and protocols.